Wortstellung der nicht-sententialen Adverbialbestimmungen im Deutschen und Chinesischen - Duanzhuang Zheng (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The present study conducts a comparative analysis of the positioning of non-sentential adverbials in German and Chinese. Considering the specific head-position-parameter, German is regarded as a derived V/2 language with underlying SOV order, while Chinese essentially represents an SVO language. Notably, despite the relatively flexible surface positions of various adverbial classes in German, they typically occupy base positions in the middle field, resulting in a standard sequence. Similarly, in Chinese, different non-sentential adverbial classes/levels can be distinguished by a specific basic sequence. The basic sequences of adverbial classes in both languages are primarily determined by the semantic domains of the adverbials and their semantic connection with the predicate or other reference word. Furthermore, the basic sequences ensure an “unmarked” information structure in both languages, with a focus projection (wider focus) only possible with regular positioning. Context-dependent modifications of the information structure lead to deviations from basic sequences. However, significant differences exist between the two languages concerning the interactions between word order and information structure, particularly regarding topic-rheme structuring, topic-comment structuring and focusbackground structuring.